Nanomolar Inhibitors of Trypanosoma brucei RNA Triphosphatase - ホー キョン; Smith Paul; Ho C Kiong; Takagi Yuko; Djaballah Hakim; Shuman Stewart (MBIO, 2016)
Eukaryal taxa differ with respect to the structure and mechanism of the RNA triphosphatase (RTPase) component of the mRNA capping apparatus. Protozoa, fungi, and certain DNA viruses have a metal-dependent RTPase that belongs to the triphosphate tunnel metalloenzyme (TTM) superfamily. Because the structures, active sites, and chemical mechanisms of the TTM-type RTPases differ from those of mammalian RTPases, the TTM RTPases are potential targets for antiprotozoal, antifungal, and antiviral drug discovery. Here, we employed RNA interference (RNAi) knockdown methods to show that Trypanosoma brucei RTPase Cet1 (TbCet1) is necessary for proliferation of procyclic cells in culture. We then conducted a high-throughput biochemical screen for small-molecule inhibitors of the phosphohydrolase activity of TbCet1. We identified several classes of chemicals-including chlorogenic acids, phenolic glycopyranosides, flavonoids, and other phenolics-that inhibit TbCet1 with nanomolar to low-micromolar 50% inhibitory concentrations (IC50s). We confirmed the activity of these compounds, and tested various analogs thereof, by direct manual assays of TbCet1 phosphohydrolase activity. The most potent nanomolar inhibitors included tetracaffeoylquinic acid, 5-galloylgalloylquinic acid, pentagalloylglucose, rosmarinic acid, and miquelianin. TbCet1 inhibitors were less active (or inactive) against the orthologous TTM-type RTPases of mimivirus, baculovirus, and budding yeast (Saccharomyces cerevisiae). Our results affirm that a TTM RTPase is subject to potent inhibition by small molecules, with the caveat that parallel screens against TTM RTPases from multiple different pathogens may be required to fully probe the chemical space of TTM inhibition.